Pendampingan Ekonomi Kreatif Pada Panti Asuhan Muhammadiyah Kota Madiun Melalui Pelatihan Pembuatan Kerajinan Tangan dan Pelatihan Pemasaran Digital - Anggita Langgeng Wijaya; Astika Kusuma Ayu Rosalianita Sari; Karuniawati Hasanah (Universitas Mathla'ul Anwar Banten, 2022)
CREATİVE ECONOMY ASSİSTANCE AT MUHAMMADİYAH ORPHANAGE İN MADİUN CİTY THROUGH HANDİCRAFT MAKİNG TRAİNİNG AND DİGİTAL MARKETİNG TRAİNİNG. This community service activity aims to provide training in making handicrafts and digital marketing training for children at the Muhammadiyah orphanage in Madiun City. This community service activity cannot be separated from implementing the Independent Learning Campus (MBKM) curriculum implemented by the Faculty of Economics and Business, Universitas PGRI Madiun. Realizing the creative economy as the downstream of independent research and humanitarian projects needs to be carried out to realize the Muhammadiyah orphanage's independence in Madiun City. Implementing the training activities is carried out by practice, presentation, and discussion. The number of participants who attended this training was 15 people. The results of this community service show an increase in the skills and knowledge of the trainees on training in making handicrafts and knowledge of digital marketing strategies. This conclusion is evidenced by an increase in the average pre-test score of 26.67 to 66.67 in the post-test score. This training has a positive impact on orphanage children in the form of additional skills in making handicrafts and additional knowledge for participants about good digital business management and motivation to develop business and entrepreneurial spirit. This training is expected to help create strong and independent foster children in the future.